Alternating Air-Medium Exposure in Rotating Bioreactors Optimizes Cell Metabolism in 3D Novel Tubular Scaffold Polyurethane Foams. Issue 2 (April 2017) - Tresoldi, Claudia; Stefani, Ilaria; Ferracci, Gaia; Bertoldi, Serena; Pellegata, Alessandro F.; Farè, Silvia; Mantero, Sara
Background: In vitro dynamic culture conditions play a pivotal role in developing engineered tissue grafts, where the supply of oxygen and nutrients, and waste removal must be permitted within construct thickness. For tubular scaffolds, mass transfer is enhanced by introducing a convective flow through rotating bioreactors with positive effects on cell proliferation, scaffold colonization and extracellular matrix deposition. We characterized a novel polyurethane-based tubular scaffold and investigated the impact of 3 different culture configurations over cell behavior: dynamic (i) single-phase (medium) rotation and (ii) double-phase exposure (medium-air) rotation; static (iii) single-phase static culture as control. Methods: A new mixture of polyol was tested to create polyurethane foams (PUFs) as 3D scaffold for tissue engineering. The structure obtained was morphologically and mechanically analyzed tested. Murine fibroblasts were externally seeded on the novel porous PUF scaffold, and cultured under different dynamic conditions. Viability assay, DNA quantification, SEM and histological analyses were performed at different time points. Results: The PUF scaffold presented interesting mechanical properties and morphology adequate to promote cell adhesion, highlighting its potential for tissue engineering purposes. Results showed that constructs under dynamic conditions contain enhanced viability and cell number, exponentially increased for double-phase rotation; under this last configuration, cells uniformly covered both the external surface and the lumen. Conclusions: The developed 3D structure combined with the alternated exposure to air and medium provided the optimal in vitro biochemical conditioning with adequate nutrient supply for cells. The results highlight a valuable combination of material and dynamic culture for tissue engineering applications.